Exact Calculation of the Product of the Hessian Matrix of Feed-Forward Network Error Functions and a Vector in 0(N) Time - Møller, Martin F. (DAIMI Report Series, 1993)
Several methods for training feed-forward neural networks require second order information from the Hessian matrix of the error function. Although it is possible to calculate the Hessian matrix exactly it is often not desirable because of the computation and memory requirements involved. Some learning techniques do, however, only need the Hessian matrix times a vector. This paper presents a method to calculate the Hessian matrix times a vector in O(N) time, where N is the number of variables in the network. This is the same order as the calculation of the gradient to the error function. The usefulness of this algorithm is demonstrated by improvement of existing learning techniques.